Analisis Efektivitas Gas Turbine Generator pada PT Mitra Energi Batam - Nur Azila; Elsya Paskaria Loyda Tarigan (Fakultas Teknik UMRI, 2023)
PT Mitra Energi Batam is one of the Gas Power Plants (PLTG) and regulates the electricity supply of Batam city with PT PLN-Batam. According to the tabulation of PT Mitra Energi Batam's production data from September 2022 to September 2023, the rolls-royce Gas Turbine Generator production engine has a downtime value of 805.60 hours. The purpose of the study is to find out the factors that cause high downtime and know how to minimize it. Using the proposed Overall Equipment Effectiveness method as a way to measure Losses due to production disruptions by taking six big loss and Fishbone diagrams to find the cause and effect of Losses that cause failure of machine or equipment operations. The results of the study of the highest OEE value in August 2023 were 98.54%, the lowest OEE value was in April 2023 which was 0%, the cause was severe damage to the power turbine blade which required engine replacement, but was constrained by the time of the engine spare delivery process. The six big Losses factor that contributed the most to the OEE value was idling minor stoppage with an average value of 8.83% and equipment failure Losses with an average value of 8.81%.